2020
DOI: 10.21203/rs.2.22898/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of the calmodulin-binding transcription activator (CAMTA) gene family in wheat (Triticum aestivum L.)

Abstract: Plant calmodulin-binding transcription activator (CAMTA) proteins play important roles in hormone signal transduction, developmental regulation, and environmental stress tolerance. However, in wheat, the CAMTA gene family has not been systematically characterized. In this work, 15 wheat CAMTA genes were identified using a genome-wide search method. Their chromosome location, physicochemical properties, subcellular localization, gene structure, protein domain, and promoter cis-elements were systematically analy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…To understand the phylogenetic relationship of olive CAMTAs, an unrooted phylogenetic tree is drawn and it is noticed that CAMTA proteins are grouped in 4 main branches and every branch contained A. thaliana CAMTA1 is present predominantly in the nuclei (Bouche et al, 2002). Also, in Fragaria × ananassa (Leng et al, 2015), P. trichocarpa (Wei et al, 2017), Gossypium species (Pant et al, 2018), in Triticum aestivum (Yang et al, 2020), in Linum usitatissimum (Ali et al, 2020), Oryza sativa (Gain et al, 2022) it was bioinformatically shown that CAMTAs are mostly localized in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the phylogenetic relationship of olive CAMTAs, an unrooted phylogenetic tree is drawn and it is noticed that CAMTA proteins are grouped in 4 main branches and every branch contained A. thaliana CAMTA1 is present predominantly in the nuclei (Bouche et al, 2002). Also, in Fragaria × ananassa (Leng et al, 2015), P. trichocarpa (Wei et al, 2017), Gossypium species (Pant et al, 2018), in Triticum aestivum (Yang et al, 2020), in Linum usitatissimum (Ali et al, 2020), Oryza sativa (Gain et al, 2022) it was bioinformatically shown that CAMTAs are mostly localized in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that fewer differentially expressed CAMTA factor genes were found in soybean roots than in soybean leaves [35]. CAMTAs have been shown to be extensively involved in plant growth and developmental regulation, as well as in biotic and abiotic stress tolerance [34]. In Arabidopsis, CAMTA1 and CAMTA2 genes use in concert with CAMTA3 to directly bind to the promoter of C-repeat binding factor2 (CBF2) to induce expression, leading to increased plant freezing tolerance.…”
Section: Analysis Of Pattern Of Camta Transcription Factors During De...mentioning
confidence: 99%
“…It has been reported that fewer differentially expressed CAMTA factor genes were found in soybean roots than in soybean leaves [35]. CAMTAs have been shown to be extensively involved in plant growth and developmental regulation, as well as in biotic and abiotic stress tolerance [34]. In Arabidopsis, CAMTA1 and CAMTA2 genes use in concert with CAMTA3 to directly bind to the promoter of C-repeat binding factor2 (CBF2) to induce expression, leading to increased plant freezing tolerance.…”
Section: Analysis Of Expression Pattern Of Camta Transcription Factors During Developmental Stagesmentioning
confidence: 99%